Eksplorasi Aren (Arenga pinnata Merr) di Tomohon, Sulawesi Utara - ELSJE T. TENDA (Pusat Penelitian dan Pengembangan Perkebunan, 2009)
ExplorationofSugar Palm (Arenga pinnata Merr) in Tomohon,North SulawesiIndonesia has high genetic diversity of sugar palm, although until now sugar palm germplasm had been collection it’s about 11 acession’s. If sugar palm acession’s not conserved, it apprehensive sugar palm’s accession which is have promising gen’s will occur genetic’s erosion. The research activity was conducted on January, 2009 at Tomohon North Sulawesi, there were Tara-tara, Pinaras and Woloan Village. The purpose of palm sugar germ plasm exploration is to increase genetic diversity of sugar palm germplasm collection which is use as breeding material in compose superior palm sugar and seeds resources in short term. The result showed that on that three villages has been found three accessions of palm sugar namely Tara-tara sugar palm, Pinaras sugar palm and Woloan sugar palm. The highest production and sugar content of toddy to be found in tall sugar palm at Tara-tara, is about 25-38 lire/bunch/day. Selection for improvement population of three accessions is needs to carry out on production and sugar content of toddy.